9y-(5y-4)=10y-(3y+2)

Simple and best practice solution for 9y-(5y-4)=10y-(3y+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9y-(5y-4)=10y-(3y+2) equation:


9y-(5y-4)=10y-(3y+2)

We simplify the equation to the form, which is simple to understand
9y-(5y-4)=10y-(3y+2)

Remove unnecessary parentheses
9y-5y+4=10y-(3y+2)

Remove unnecessary parentheses
9y-5y+4=10y-3y-2

We move all terms containing y to the left and all other terms to the right.
+9y-5y-10y+3y=-2-4

We simplify left and right side of the equation.
-3y=-6

We divide both sides of the equation by -3 to get y.
y=2

See similar equations:

| inx^3=6 | | 45x-37y+87= | | 17-2p=4p | | 12x-11=64 | | -7(-6+9f)+3= | | 79-13= | | 9(-4z+5)-8= | | 3z^2-0.75=90 | | x+9=4(x-1)(x-1) | | 7+13x=11+13x | | 3(6x+8)=9x-16-x | | -8x-3=-48 | | 5x+2y=12findy | | y=x^2-2x-6y=4x+10 | | -16x^2+128x+2=0 | | (3x+2x+2+2x+2+5x+3)5= | | (-2x+3)(-x+15)=15 | | 2(x-6)=9-5x | | 6w-10w^3= | | (-2x)+(-x-16)=0 | | log(a)4=2 | | 3(x-2)=2x+2(x-8) | | 25(4-2x)=5(-6x) | | (5x-2)=(9x) | | -3(m+2)+6m=9(m+-1) | | 9a+33ab+-76b+65c+17a+51ab+-80b+13c= | | 3+16x+12=11x+15+5x | | -2c+3.7=-0.5 | | 21ab+-50b+13c+17a+30ab+-30b= | | 6x-42=9x | | 12x+2=12x-5 | | 9a+12ab+-26b+52c+21ab+-50b+13c= |

Equations solver categories